Automatic Generation of Graceful Programs - Yiyan Lin; Kulkarni, S. (2012 IEEE 31st Symposium on Reliable Distributed Systems, 2012)
Traditionally, (nonmasking and masking) fault tolerance has focused on ensuring that after the occurrence of faults, the program recovers to states from where it continues to satisfy its original specification. However, a problem with this limited notion is that, in some cases, it may be impossible to recover to states from where the entire original specification is satisfied. For this reason, one can consider a fault-tolerant graceful-degradation program that ensures that upon the occurrence of faults, the program recovers to states from where a (given) subset of its specification is satisfied. Typically, the subset of specification satisfied thus would be the critical requirements. In this paper, we focus on automatically revising a given program to obtain a corresponding graceful program, i.e., a program that satisfies a weaker specification. Specifically, this step involves adding new behaviors that satisfy the given subset of specification. Moreover, it ensures that during this process, it does not remove any behavior from the original program. With this motivation, in this paper, we focus on automatic derivation of the graceful program, i.e., a program that contains all behaviors of the original program and some new behaviors that satisfy the weaker conditions. We note that this aspect differentiates this work from previous work on controller synthesis as well as automated addition of fault tolerance in that this work requires that no new behaviors are added in the absence of faults.